Smart automation system based on field programmable gate array - Taslim, Fatima Nafsia; Ahona, Tasfia Lamisa; Tasnim, Nishat; Haque, Nazifa Rezwana (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.